Penguatan Sistem Merit Aparatur Sipil Negara melalui Tata Kelola Assessment Center dan Pemanfaatan Hasil Penilaian Kompetensi: Sintesis Studi Multikasus di Pemerintah Kota Palembang - Bachtari Alam Hidayat; Putri Erlyn; Herie Saksono (Research and Development Agency Ministry of Home Affairs, 2026)
The merit system is central to Indonesia’s bureaucratic reform agenda, which seeks professional, objective, and competency-based civil service governance. The assessment center is among the principal instruments developed to support it, yet many local governments still struggle to ensure that assessment results actually inform personnel decisions. This study analyzes the relationship between assessment center implementation and the utilization of assessment results in strengthening the civil service merit system in the Palembang City Government, and formulates a governance model integrating the two. A qualitative multi-case design was used. The first case examined assessment center implementation at the Palembang City Civil Service and Human Resources Development Agency; the second examined the utilization of assessment results. Data were collected through in-depth interviews, observation, and documentary analysis of regulations, official reports, and institutional records, and their credibility was established through source triangulation. The data were analyzed using thematic cross-case synthesis. The findings indicate that assessment center implementation is supported by institutional arrangements, regulations, and relatively adequate assessment mechanisms, but that assessment results are not yet fully utilized in personnel decision-making, resulting in a gap between the institutional capacity of the assessment center and the utilization of its outputs within the merit system. The study proposes an integrated assessment governance model comprising institutional capacity, competency intelligence, governance integration, and merit system strengthening, and offers it as a reference for competency-based talent management policy and for sustaining merit system implementation at the local level.